Comparison of enteral nutrition with total parenteral nutrition for patients with locally advanced unresectable esophageal cancer harboring dysphagia in definitive chemoradiotherapy. (20th June 2019) - Furuta, Mitsuhiro; Yokota, Tomoya; Tsushima, Takahiro; Todaka, Akiko; Machida, Nozomu; Hamauchi, Satoshi; Yamazaki, Kentaro; Fukutomi, Akira; Kawai, Sadayuki; Kawabata, Takanori; Onozawa, Yusuke; Yasui, Hirofumi
Abstract : Enteral nutrition is advantageous for improving serum albumin level, and reducing hematological toxicity and duration of hospitalization compared with total parenteral nutrition during definitive chemoradiotherapy for unresectable esophageal cancer. Abstract: Background: The nutritional status of patients with esophageal squamous cell carcinoma (ESCC) harboring dysphagia is often poor. The efficacy and safety of enteral nutrition (EN) versus total parenteral nutrition (TPN) have not been addressed in patients with ESCC requiring nutritional support during definitive chemoradiotherapy (dCRT). Methods: We performed a retrospective analysis of 51 locally advanced unresectable ESCC patients with dysphagia receiving EN ( n = 28) or TPN ( n = 23) during dCRT between 2009 and 2016. Results: Patient characteristics in EN vs. TPN were as follows: median age (range), 67 (34 to 82) vs. 66 (57 to 83); ECOG performance status 0/1/2, 11/15/2 vs. 7/14/2; dysphagia score 2/3/4, 11/15/2 vs. 14/8/1; and primary tumor location Ce/Ut/Mt/Lt/Ae, 4/6/14/3/1 vs. 2/2/16/1/2. Median changes in serum albumin level one month after dCRT were +8.8% (−36 to 40) in EN and −12% (−64 to 29) in TPN ( P = 0.00377). Weight, body mass index, and skeletal muscle area were not significantly different between the groups. Median durations of hospitalization were 50 days (18 to 72) in EN and 63 days (36 to 164) in TPN ( P = 0.00302). Adverse events during dCRT in EN vs. TPN were as follows: catheter-related infection, 0 vs. 6 (27%); aspiration pneumonia, 3 (11%) vs. 2 (9%); mediastinitis, 3 (11%) vs. 1 (5%); grade ≥3 neutropenia, 6 (21%) vs. 14 (64%) ( P = 0.00287); and febrile neutropenia, 0 vs. 6 (27%) ( P = 0.00561). Conclusions: EN may be advantageous for improving serum albumin level, and reducing hematological toxicity and duration of hospitalization compared with TPN during dCRT in ESCC patients.